2018
DOI: 10.1108/jeee-08-2017-0053
|View full text |Cite
|
Sign up to set email alerts
|

Performance-oriented factors for women entrepreneurs – a scale development perspective

Abstract: Purpose The purpose of this study is to conceptualize, develop and validate a scale reflecting performance dimensions of women entrepreneurs. The study intends to address the important aspects of women entrepreneur such as identifying factors influencing performance of women entrepreneur in emerging economies including India, and to develop a reliable and valid scale for measuring performance from women entrepreneurs’ perspective, which will help to explain the phenomena of entrepreneurship among women by usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 89 publications
0
32
0
2
Order By: Relevance
“…Iran is an important case among the developing countries by being the second-mostpopulous country in the MENA region and the 18th worldwide with almost 81 m population (Cheratian et al, 2019). Like their counterparts in other emerging economies, Iranian women entrepreneurs face various challenges such as lack of access to potential lucrative opportunities (Jha et al, 2018).…”
Section: Iranian Women Entrepreneursmentioning
confidence: 99%
“…Iran is an important case among the developing countries by being the second-mostpopulous country in the MENA region and the 18th worldwide with almost 81 m population (Cheratian et al, 2019). Like their counterparts in other emerging economies, Iranian women entrepreneurs face various challenges such as lack of access to potential lucrative opportunities (Jha et al, 2018).…”
Section: Iranian Women Entrepreneursmentioning
confidence: 99%
“…This is to mean that lack of training could have an effect in women entrepreneurs to explore the personal entrepreneurial competence that might help them improve their business success (Gizaw et al, 2019). Moreover, the findings of Jha et al (2018) suggested that a customized training program for women entrepreneurs is essential at each stage of businesses to enhance the enterprises' success. Therefore, women entrepreneurs perform better in their business when they access business training (Mandawa, 2016).…”
Section: Business Trainingmentioning
confidence: 99%
“…In other words, adequate supplies of raw materials ensure good performance of firms and unavailability of raw materials can be a barrier for success. Therefore, access to market and micro and small enterprises' performance have a positive relationship (Jha et al, 2018).…”
Section: Access To Marketmentioning
confidence: 99%
“…The literature has paid a lot of attention to the gender gap in the labour market and the glass-ceiling effect (Cotter et al , 2001; Bosse and Porcher, 2012) and recently has begun to also point out gender dynamics in entrepreneurship (Brush et al , 2014b; Gompers and Wang, 2017; Jha et al , 2018), exploring the barriers that female entrepreneurs face starting and growing their businesses (Roper and Scott, 2009). To make a right assessment of these barriers, we will conduct a systematic literature review of entrepreneurship financing.…”
Section: Introductionmentioning
confidence: 99%